A Malik Bennabi reader: a Muslim visionary in the whirlwind of colonial modernity. Vol. 2. - El Mesawi, Mohamed El Tahir (International Institute of Islamic Thought (IIIT), Internal Institute for Muslim Unity (IIMU), IIUM and Islamic Book Trust, 2025)
This book represents an attempt to provide a comprehensive translation of Malik Bennabi’s intellectual work, offering insight into the central themes that occupied his mind throughout his career as a thinker and writer. with the objective of introducing the reader to the central themes that occupied Bennabi’s mind throughout his career as a thinker and writer. The second volume of the book covers three of those themes: politics, economics and Islam and Muslims in the modern world.